Pancasila as a Normative Framework for Social Justice-based Natural Resource Management in Indonesia - Rochmad Abu Bakar; Vernando; Ayuni Asita Hadiyati (Journal of Communication, Sustainability, and Empowerment, 2026)
This study examines Pancasila as a normative framework for socially just natural resource governance in Indonesia. Although natural resources are constitutionally intended to be controlled by the state and utilised for the greatest prosperity of the people, the practice of natural resource governance still reveals various problems, including resource conflicts, unequal control, weak benefit distribution, limited community participation, and ecological degradation. This study employed a qualitative method based on a systematic literature review by identifying, classifying, and analysing relevant literature, legal norms, and academic studies. The findings show that Pancasila, particularly the principle of social justice, can be operationalised as an evaluative and prescriptive parameter in natural resource governance. This parameter includes five main dimensions: state control, resource utilisation, benefit distribution, community participation, and environmental sustainability. The study concludes that socially just natural resource governance must not be oriented merely toward economic growth, investment, and state revenue, but also toward equitable welfare, protection of affected communities, meaningful participation, and ecological sustainability